Effects of plant growth regulators on lentil (Lens culinaris Medik.) cultivars (Bangladesh Journal of Botany, 2015)
Lentil (Lens culinaris Medik.) is an annual pulse legume crop of immense economic importance. This study reports use of 16 lentil cultivars' shoot tips, internode, hypocotyl, cotyledon and root explants cultured on MS medium containing 3 mg/l BAP-0.5 mg/l 2,4-D or 0.25 mg/l IBA for shoot regeneration. The results showed maximum shoot regeneration from cv. Yesil 21 on internode explants on 3mg/l BAP-0.5 mg/l 2,4-D. Best shoot regeneration on MS medium containing 0.25 mg/l IBA was noted on internode explants of cv. Seyran 96. In general shoot regeneration on 0.25 mg/l IBA was better compared to 3mg/l BAP and 0.5 mg/l 2,4-D. Well developed shoots from all cultivars regenerated on both types of culture media were rooted on MS medium containing 0.19 mg/l NAA. A system to regenerate lentil is established that will help in easy genetic transformation in future. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22727 Bangladesh J. Bot. 44(1): 79-84, 2015 (March